Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subset - Lehmann, C. H. K.; Baranska, A.; Heidkamp, G. F.; Heger, L.; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, M.; Kießling, Melissa; et al. (2017)
EVALuna2:33396

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, Michaela; Kießling, Melissa; et al. (2017)
EVALuna2:33397

DC subset–specific induction of T cell responses upon antigen uptake via Fcγ receptors in vivo - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, Kirsten; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, Simone; Seeling, Michaela; Kießling, Melissa; et al. (Journal of Experimental Medicine, 2017)
Dendritic cells (DCs) are efficient antigen-presenting cells equipped with various cell surface receptors for the direct or indirect recognition of pathogenic microorganisms. Interestingly, not much is known about the specific expression pattern and function of the individual activating and inhibitory Fcγ receptors (FcγRs) on splenic DC subsets in vivo and how they contribute to the initiation of T cell responses. By targeting antigens to select activating and the inhibitory FcγR in vivo, we show that antigen uptake under steady-state conditions results in a short-term expansion of antigen-specific T cells, whereas under inflammatory conditions especially, the activating FcγRIV is able to induce superior CD4+ and CD8+ T cell responses. Of note, this effect was independent of FcγR intrinsic activating signaling pathways. Moreover, despite the expression of FcγRIV on both conventional splenic DC subsets, the induction of CD8+ T cell responses was largely dependent on CD11c+CD8+ DCs, whereas CD11c+CD8− DCs were critical for priming CD4+ T cell responses.<br
Keywords: Infectious disease and host defense; Innate immunity and inflammation; Tolerance

Dendritic cells are involved in the resolution of inflammation by IVIg in arthritis - Lehmann, Christian; Amon, Lukas; Seichter, A.; Brückner, Christin; Altmann, Leon; Heger, Lukas; Heger, L.; Ravetch, J. V.; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Sweet SIGNs: IgG glycosylation leads the way in IVIG-mediated resolution of inflammation - Brückner, Christin; Lehmann, Christian; Dudziak, Diana; Nimmerjahn, Falk (International Immunology, 2017)
A hallmark of many chronic inflammatory and autoimmune diseases is that there is an impaired resolution of inflammation and return to the steady state. The infusion of high doses of pooled serum IgG preparations from thousands of donors [intravenous immunoglobulin (IVIG) therapy] has been shown to induce resolution of inflammation in a variety of chronic inflammatory and autoimmune diseases, suggesting that IgG molecules can instruct the immune system to stop inflammatory processes and initiate the return to the steady state. The aim of this review is to discuss how insights into the mechanism of IVIG activity may help to understand the molecular and cellular pathways underlying resolution of inflammation. We will put a special emphasis on pathways dependent on the IgG FC domain and IgG sialylation, as several recent studies have provided new insights into how this glycosylation-dependent pathway modulates innate and adaptive immune responses through different sets of C-type or I-type lectins.
EVALuna2:34371

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy